2020
DOI: 10.1021/acsnano.0c02618
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: A Call for Physical Scientists and Engineers

Abstract: The COVID-19 pandemic is one of those global challenges that transcends territorial, political, ideological, religious, cultural, and certainly academic boundaries. Public health and healthcare workers are at the frontline, working to contain and to mitigate the spread of this disease. Although intervening biological and immunological responses against viral infection may seem far from the physical sciences and engineering that typically work with inanimate objects, there actually is much that canand shouldb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
226
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(235 citation statements)
references
References 31 publications
0
226
0
9
Order By: Relevance
“…These airborne viruses contaminate the ambience and settle on surfaces. Huang et al ( 2020 ) explain how fomites formed from deposited droplets are potentially infectious. The pathways for infection explained by Huang et al ( 2020 ) creates a need for an understanding of the process of reducing the fomites and virus laden airborne droplets to break the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These airborne viruses contaminate the ambience and settle on surfaces. Huang et al ( 2020 ) explain how fomites formed from deposited droplets are potentially infectious. The pathways for infection explained by Huang et al ( 2020 ) creates a need for an understanding of the process of reducing the fomites and virus laden airborne droplets to break the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al ( 2020 ) explain how fomites formed from deposited droplets are potentially infectious. The pathways for infection explained by Huang et al ( 2020 ) creates a need for an understanding of the process of reducing the fomites and virus laden airborne droplets to break the spread of COVID-19. Diwan et al ( 2020 ) simulated dry cough and showed a drop in temperataure of cough-fluid along with a lateral spread of flow due to turbulent entrainment.…”
Section: Introductionmentioning
confidence: 99%
“…The virus replicates in the upper and lower respiratory tract, forming lesions (Chan, Yuan, et al., 2020 ). The general symptoms observed in the infected individuals are fever, cough, dyspnoea and lesion in the lungs (Huang et al., 2020 ). In the advanced stage, the symptoms of this virus show pneumonia which progresses to severe pneumonia and acute respiratory distress syndrome (ARDS) which results in the need for life-support to sustain the patient's life (Lai et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There should be many ways to set up physicochemical barriers to drastically reduce the number and viability of the viruses before they reach the host and breach the last line of biological and immunological defenses. 2 Public health measures to control and mitigate any infectious diseases must address one or more of the three necessary steps required for transmission ( Figure 1 ). This includes identifying and isolating the source, breaking the chain of transmission, and protecting the susceptible hosts.…”
Section: Introductionmentioning
confidence: 99%